Evaluation of the presence of allergens in children's products available for sale in a big city - Rosana Lazzarini; Mariana de Figueiredo Silva Hafner; Mayara Gomes Rangel (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Children's products are considered safe by the general population and doctors. Labels with terms such as "hypoallergenic" or "dermatologically recommended and tested" denote trust and credibility with the idea that they can be used by any individual. Patients with allergic contact dermatitis may be sensitive to allergens present in any product, including children's. There is insufficient knowledge about allergens in these products in our country. We evaluated 254 children's products, and at least one allergen was present in 236 (93%) of them. The indication of a topical product should be careful and based on contact tests.